2012
DOI: 10.1021/jo2024569
|View full text |Cite
|
Sign up to set email alerts
|

Multigram Synthesis of Isobutyl-β-C-galactoside as a Substitute of Isopropylthiogalactoside for Exogenous Gene Induction in Mammalian Cells

Abstract: Herein we report that isobutyl-β-C-galactoside (IBCG) is also a promising inducer of gene expression in mammalian cells and report a new synthetic route to the compound that should make obtaining the multigram quantities of material required for animal studies more feasible. A convenient synthesis of IBCG, an inducer of genes controlled by the lac operon system in bacterial cells, was achieved in 5 steps from galactose in 81% overall yield without any chromatographic separation steps. An optimized microwave-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The catalytic hydrogenation was readily applicable to C-glycosides derived from ribofuranose (2af) and galactose (2ag). Importantly, the present protocol is even suitable for the hydrogenation of an unprotected galactose derivative and afforded the gene inducer isobutyl-β-C-galactoside (IBCG, 2ah) 66 in 89% yield.…”
Section: Entrymentioning
confidence: 99%
“…The catalytic hydrogenation was readily applicable to C-glycosides derived from ribofuranose (2af) and galactose (2ag). Importantly, the present protocol is even suitable for the hydrogenation of an unprotected galactose derivative and afforded the gene inducer isobutyl-β-C-galactoside (IBCG, 2ah) 66 in 89% yield.…”
Section: Entrymentioning
confidence: 99%
“…Substitution of the glycosidic oxygen atom with sulfur [3537] or carbon [38,39] is a now common method to enhance stability of glycosides. Substitution of the pyranose oxygen, such as in 5- S glycosides, can possibly minimize structural changes [40] and such sugar mimics have shown increased cytotoxic activity towards cancer cell lines compared to their O counterpart [41].…”
Section: Non-natural Sugars To Enhance Glycoside Stabilitymentioning
confidence: 99%
“…[2] For example, we recently demonstrated that the protecting groups greatly influence the reactivity of intermediates in the synthesis a carba-sugar. [3] The protecting groups on the donor and acceptors also play key roles in determining outcomes in glycosylation reactions. [4] For example, we recently noted that a fluorous phosphate protecting group could change the stereochemical out of a glycosylation unexpectedly.…”
Section: Introductionmentioning
confidence: 99%
“…The chosen protecting groups are much more than inert groups in carbohydrates synthesis, since they can also have a profound impact on the reactivity in glycosylation of the substrate 2. For example, we recently demonstrated that the protecting groups greatly influence the reactivity of intermediates in the synthesis a carba‐sugar 3. The protecting groups on the donor and acceptors also play key roles in determining outcomes in glycosylation reactions 4.…”
Section: Introductionmentioning
confidence: 99%